2014
DOI: 10.1007/s40615-014-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

African-American Womens’ Eating Habits and Intention to Change: a Pilot Study

Abstract: Unhealthy diet is one of the leading contributors for chronic disease related morbidity and mortality in African-American (AA) women living in the USA. The purpose of this study was to describe eating habits and intention to change using the stages of change (SOC) model in a sample of AA women. A cross-sectional population-based study was conducted in Florida with AA women. A total of 292 AA women participated. Outcome variables were eating breakfast, foods having low to no fat, fruits and vegetables, whole gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…Health promotion programs should become an integral part of academic- community collaborative agreements. Understanding the stages of change can be helpful for developing interventions for improving eating habits [ 7 ]. Building awareness of the benefits and barriers of eating healthy is a good first step to address the importance of good dietary practices in maintaining cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health promotion programs should become an integral part of academic- community collaborative agreements. Understanding the stages of change can be helpful for developing interventions for improving eating habits [ 7 ]. Building awareness of the benefits and barriers of eating healthy is a good first step to address the importance of good dietary practices in maintaining cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Such an increase will draw attention to the importance of healthy eating, can lead to positive health benefits and the possibility of increasing lifespan. Research has shown that unhealthy diet is a primary risk factor for developing chronic disease that results in excessive morbidity and mortality among African Americans [ 7 ]. Other factors affect the dietary choices of African American low-income women who reside in urban communities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28%, respectively) (Webb et al, 2014). Skipping breakfast and frequent consumption of soda/sugar-sweetened beverages are eating patterns reported to contribute to obesity (Blondin, Anzman-Frasca, Djang, & Economos, 2016;Boggs et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…From adolescence to adulthood, African-American females face several challenges to eating healthy, engaging in adequate exercise, and maintaining health body weight. In all of these health behaviors, there is a greater potential role of modifying social support and implementing community-based interventions for African-American females across life span [10, 11, 33]. …”
Section: Discussionmentioning
confidence: 99%